The Results of Posteromedial Release (Turco Method) for the Treatment of Congenital Clubfoot in Children between 6 Months to Five Years Old - S.H Ayatollahi -Moussavi (Journal of Kerman University of Medical Sciences, 2004)
In this prospective study 37 children (65 feet) between 6 months and 5 years old have been chosen. In 75% of cases the disease was bilateral, 23 patients were male and 14 female. There was not family history of congenital clubfoot in any case. The mean age of surgery was 20.3 months (6-56 months). All patients underwent PMR (Turco method) with two consequent corrective casts under general anesthesia and then clubfoot shoes was ordered. Early post-operative complications happened in six cases (blister, edema & infection). Radiographic evaluations was made before operation, immediately after operation, and as late follow up. Correction achieved in all patients according to immediate post-operative X-rays. After mean follow up of 24.3 months 48 feet (73%) had excellent to good results, 13 feet (20%) fair and 4 feet (6%) failure (according to turco criteria). Out of 17 feet with recurrence of deformity, the metarsus adductus was most common (13 feet). All children with recurrence of deformity were over 2 years of age at the time of surgery with upper range of age and 4 cases (6 feet) ignored ordered regular casting & shoe wearing. It seems that this method of surgery is effective procedure for correction of deformity for children under 5 years old but best results obtained for children under 2 years old..